A heme‐binding protein produced by Haemophilus haemolyticus inhibits non‐typeable Haemophilus influenzae. Issue 2 (2nd December 2019) - Latham, Roger D.; Torrado, Mario; Atto, Brianna; Walshe, James L.; Wilson, Richard; Guss, J. Mitchell; Mackay, Joel P.; Tristram, Stephen; Gell, David A.
Abstract: Commensal bacteria serve as an important line of defense against colonisation by opportunisitic pathogens, but the underlying molecular mechanisms remain poorly explored. Here, we show that strains of a commensal bacterium, Haemophilus haemolyticus, make hemophilin, a heme‐binding protein that inhibits growth of the opportunistic pathogen, non‐typeable Haemophilus influenzae (NTHi) in culture. We purified the NTHi‐inhibitory protein from H. haemolyticus and identified the hemophilin gene using proteomics and a gene knockout. An x‐ray crystal structure of recombinant hemophilin shows that the protein does not belong to any of the known heme‐binding protein folds, suggesting that it evolved independently. Biochemical characterisation shows that heme can be captured in the ferrous or ferric state, and with a variety of small heme‐ligands bound, suggesting that hemophilin could function under a range of physiological conditions. Hemophilin knockout bacteria show a limited capacity to utilise free heme for growth. Our data suggest that hemophilin is a hemophore and that inhibition of NTHi occurs by heme starvation, raising the possibility that competition from hemophilin‐producing H. haemolyticus could antagonise NTHi colonisation in the respiratory tract. Abstract : Here, we show that strains of commensal H. haemolyticus secrete hemophilin, a protein with a previously undescribed heme‐binding protein fold. In culture, hemophilin sequesters environmental heme and makes this essential nutrient available to H. haemolyticus while blocking uptake by H. influenzae, an opportunistic pathogen that occupies the same ecological niche in the respiratory tract and also relies on heme scavenging for its survival.